2016
DOI: 10.3389/fnagi.2016.00081
|View full text |Cite
|
Sign up to set email alerts
|

Glial Modulation by N-acylethanolamides in Brain Injury and Neurodegeneration

Abstract: Neuroinflammation involves the activation of glial cells and represents a key element in normal aging and pathophysiology of brain damage. N-acylethanolamides (NAEs), naturally occurring amides, are known for their pro-homeostatic effects. An increase in NAEs has been reported in vivo and in vitro in the aging brain and in brain injury. Treatment with NAEs may promote neuroprotection and exert anti-inflammatory actions via PPARα activation and/or by counteracting gliosis. This review aims to provide an overvie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 102 publications
(215 reference statements)
1
16
0
Order By: Relevance
“…Furthermore, our findings agree with previous reports on the protective effects of PEA in experimental neurodegeneration (Skaper et al, 1996;Esposito et al, 2012;Scuderi et al, 2014;Herrera et al, 2016). PEA protected from the decrease in MAP-2 expression induced by amyloid peptides (Scuderi et al, 2014;Tomasini et al, 2015) and by MPTP in an animal model of Parkinson's disease (Esposito et al, 2012).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Furthermore, our findings agree with previous reports on the protective effects of PEA in experimental neurodegeneration (Skaper et al, 1996;Esposito et al, 2012;Scuderi et al, 2014;Herrera et al, 2016). PEA protected from the decrease in MAP-2 expression induced by amyloid peptides (Scuderi et al, 2014;Tomasini et al, 2015) and by MPTP in an animal model of Parkinson's disease (Esposito et al, 2012).…”
Section: Discussionsupporting
confidence: 92%
“…One month after a severe, 20-min PA, the rats developed an alteration in the endocannabinoid system expression and related acylethanolamide pathways (Blanco et al, 2015). Palmitoylethanolamide (PEA) is an endogenous lipidic neuromodulator related to endocannabinoids, acting as a peroxisome proliferator-activated receptor alpha (PPARα) or G protein-coupled receptor 55 (GPR55) agonist that elicits anti-inflammatory, neuroprotective, and restorative properties (Mattace Raso et al, 2014;Petrosino and Di Marzo, 2017) in vitro (Avagliano et al, 2016), in animal models of both neurodegeneration (Esposito et al, 2011(Esposito et al, , 2012(Esposito et al, , 2014Herrera et al, 2016) and hypoxia-ischemia (HI) (Fernandez-Lopez et al, 2013;England et al, 2015), and in human patients as well (Orefice et al, 2016). Interestingly, one study reported that natives from Puno at about 3,830 m above sea level in Peru, having high hemoglobinemia and low oxygen saturation, also exhibited a high plasma concentration of PEA (Alarcon-Yaquetto et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The exact mechanism of PEA action remains to be elucidated in further studies. Nevertheless, emerging evidence supports the notion that the neuroprotective and anti-inflammatory effect of PEA occurs through complex mechanisms involving interactions between microglial and non-neuronal cells of immune origin such as mast cells in the CNS, and with mast cells and macrophages in the periphery (Skaper et al, 2013 ; Herrera et al, 2016 ; Guida et al, 2017 ). In periphery, PEA completely reverses the upregulation of eCBs and eiCs, e.g., 2-AG and PGE 2 in acute phase and maintains low the level of AEA-AA till acute phase, likely in order to tune down the rise of KA-derived peripheral inflammation by restricting the AA pool for PGs synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…OEA, a monounsaturated lipid mediator and a bioactive molecule, belongs to the acyethanolamides family ( Figure 2) is synthesized in the proximal small intestine from oleic acid and phosphatidylethanolamine by N-acyltransferase (NAT) enzyme in the cellular membrane (Brown, Karimian Azari, & Ayala, 2017). OEA also is expressed in other tissues such as adipose tissues (Schmid, Wold, Krebsbach, Berdyshev, & Schmid, 2002), neurons (Hu & Mackie, 2015), and astrocytes (Herrera, Kölliker-Frers, Barreto, Blanco, & Capani, 2016).…”
Section: Various Nutraceutical and Pharmaceutical Compounds Have Beenmentioning
confidence: 99%